Full surplus extraction from colluding bidders - Daniil Larionov (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
I consider a repeated auction setting with colluding buyers and a seller who adjusts reserve prices over time without long-term commitment. To model the seller's concern for collusion, I introduce a new equilibrium concept: collusive public perfect equilibrium. For every strategy of the seller I define the corresponding "buyer-game" in which the seller is replaced by Nature who chooses the reserve prices for the buyers in accordance with the seller's strategy. A public perfect equilibrium is collusive if the buyers cannot achieve a higher symmetric public perfect equilibrium payoff in the corresponding buyer-game. In a setting with symmetric buyers with private binary iid valuations and publicly revealed bids, I find collusive public perfect equilibria that allow the seller to extract the entire surplus from the buyers in the limit as the buyers' discount factor goes to 1. I therefore show that a non-committed seller can effectively fight collusion even when she faces patient buyers, can only set reserve prices, and has to satisfy stringent public disclosure requirements.
Keywords: 330